LA GESTIÓN PARA LA MEJORA DE PROCESOS: PROPUESTA PARA EL CAMBIO Y EVALUACIÓN DE LOS PROCESOS LOGÍSTICOS EN EL SECTOR DE LAS TELECOMUNICACIONES - Angélica Lizeth Martínez Ramírez; Cristian Camilo Urrego Barrios; Ever Ángel Fuentes Rojas (Revista Ingeniería, Matemáticas y Ciencias de la Información)
Process management provides a vision and tools with which you can improve and redesign the workflow to make it moreefficient and adapted to the needs of all users. Process management approaches are an advantageous proposal for theimprovement of management, which is why in this article a work is proposed to standardize logistics processes in acompany in the telecommunications sector as a solution for change. To this end, the methodology is based on adiagnosis as a result of a pre-contextualization and based on the application of analysis tools, a proposal for improvementinvolving structuring, updating, thread documentation and study of working times, and finally an analysis of researchimpact resulting in an 11% decrease in documentation and expanding the scope of each of the threads and 21% in theexecution times of the activities.